S-Methyl-(2-Methoxycarbonylamino-Benzimidazole-5) Thiosulfonate as a Potential Antiparasitic Agent-Its Action on the Development of Ascaris suum Eggs In Vitro - Małgorzata Dmitryjuk; Magdalena Szczotko; Katarzyna Kubiak; Radosław Trojanowicz; Zhanna Parashchyn; Halyna Khomitska; Vira Lubenets (MDPI AG, 2020)
Ascaris suum is a soil-transmitted parasite causing ascariasis in pigs, largely limiting livestock production globally. Searching for new drugs affecting all stages of nematode development is necessary and widely postulated. The in vitro activity of S-methyl-(2-methoxycarbonylamino-benzoimidasole-5) thiosulfonate on A. suum developing eggs was studied. Five concentrations of the drug were used-0.625, 1.25, 2.5, 5 and 10 mM during 24, 48 and 72 h of exposure. After drug treatment, the eggs were washed and cultured in 0.05 M HCl at 27 °C for 20 days. Both the concentration and duration of the drug exposure had an inhibitory impact on the percentage of L2 larvae developed. The best effect was obtained after 72 h of incubation in 5 mM drug solution, only 1.9 ± 3.3% of the larvae developed to the L2 stage. Moreover, no SNP was detected at codon 167, which is correlated with benzimidazole resistance, in the tested samples. For the first time, it has been demonstrated that S-M-(2-MKA-BZ-5)TS seems to be a potential ovicidal anti-helminthic agent. It may lead to the elimination of parasites and reduce environmental contamination from roundworm eggs. The ovicidal effects of the drug should be additionally confirmed by further infection studies using experimental animals.